Proficiência escritora no ensino médio : a didatização dos conhecimentos indispensáveis para a produção de um texto dissertativo-argumentativo - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
Text production in the Enem exam assesses students’ argumentative and writing skills, as well as their competence in interpreting current issues. High school graduates are required to defend a point of view on socially relevant matters, presenting consistent arguments and a proposal for intervention. The assessment of these abilities goes beyond the evaluative context, establishing itself as an essential formative process for every student in basic education. In this regard, this research analyzed the essential knowledge required for the production of argumentative essays in High School, aiming to map and relate them to the Base Nacional Comum Curricular (National Common Core Curriculum) and to systematize them into a didactic pathway that supports teachers in guiding their pedagogical practice. Grounded in theoretical references such as Bronckart (1999), Adam (2019), Marcuschi (2008), Sena (2017), Garcia (2010), and Koch (2011, 2015, 2016), the investigation mapped and categorized the essential knowledge for the production of argumentative-essay texts present in the competencies of the National High School Exam writing test, in addition to correlating them with the skills outlined in the Portuguese Language curriculum, before proposing a didactic pathway. The results indicated that the essential knowledge of argumentative-essay texts included in the Enem writing competencies are linguistic, discursive, textual, and sociocultural, and are embedded in the National Common Curricular Base, specifically in skills from the field of Languages and its Technologies, the journalistic-media field, and across all domains. Furthermore, the investigation revealed that the didactic pathway requires the articulation of communicative, thematic, and formal dimensions and can be structured around the stages of text production. It is concluded that the mapping of this knowledge and the proposition of a didactic pathway opens up possibilities for teachers to work on text production in high school, thereby contributing to civic education.
Writing proficiency in high school : the didacticization of the indispensable knowledge for the production of an argumentative-essay text
Keywords: Ensino; Língua portuguesa; Ensino médio; Produção textual; Texto dissertativo-argumentativo; Teaching; Portuguese language; High school; Text production; Argumentative essay; LINGUISTICA, LETRAS E ARTES::LINGUISTICA